Update on Tenosynovial Giant Cell Tumor, an Inflammatory Arthritis With Neoplastic Features - Robert, Marie; Farese, Helena; Miossec, Pierre (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory disease that leads to joint destruction and bone erosion. Even if many treatments were developed with success in the last decades, some patients fail to respond and disease chronicity is still a burden. Mechanisms involved in such resistance may include molecular changes in stromal cells. Other explanations can come from observations of tenosynovial giant cell tumor (TGCT), also called pigmented villonodular synovitis, considered as an inflammatory arthritis with features of cancer. TGCT leads to synovium hypertrophy and hyperplasia with hemosiderin deposition. It affects young adults, resulting in secondary osteoarthritis and increased morbidity. TGCT shows clinical, histological and genetic similarities with RA but affecting a single joint. However, the monoclonality of some giant cells, the presence of translocations and rare metastases also suggest a neoplastic disease, with some features common with sarcoma. TGCT is more probably in an intermediate situation between an inflammatory and a neoplastic process, with a main involvement of the proinflammatory cytokine CSF-1/CSF1R signaling axis. The key treatment option is surgery. New treatments, derived from the RA and sarcoma fields, are emerging. The tyrosine kinase inhibitor pexidartinib was recently FDA-approved as the first drug for severe TGCT where surgery is not an option. Options targeting directly the excessive proliferation of synoviocytes are at a preclinical stage.